Association between Age and Changes in Heart Rate Variability after Hemodialysis in Patients with Diabetes - Niu, Sheng-Wen; Huang, Jiun-Chi; Chen, Szu-Chia; Lin, Hugo Y.-H.; Kuo, I.-Ching; Wu, Pei-Yu; Chiu, Yi-Wen; Chang, Jer-Ming (Frontiers in Aging Neuroscience, 2018)
Background: Heart rate variability (HRV) represents changes in the time between successive heart beats, and it has been used to assess the autonomic nervous system. Previous studies have reported autonomic dysfunction in diabetic patients undergoing hemodialysis (HD), however no studies have evaluated the effects of age on changes in HRV in these patients. The aim of this study was to examine the effects of age on changes in HRV in diabetic HD patients. Methods: We enrolled 84 diabetic patients receiving maintenance HD. HRV was measured before and after HD to assess changes in HRV (ΔHRV). The patients were divided into two groups based on their age (< or ≥ 65 years). Results: Compared to the patients aged < 65 years, those aged ≥ 65 years had a higher high frequency (HF) % (p = 0.032) before HD. The patients aged < 65 years had a significant increase in very low frequency, low frequency (LF), and HF after HD. The patients aged ≥ 65 years had a significant increase in LF, but a significant decrease in HF% after HD. There was a significant interaction between age and change of HF% (p = 0.023) after HD. After multivariate adjustments for clinical, biochemical data and medications, systolic blood pressure, total cholesterol, hemoglobin, and hemoglobin were associated with ΔLF, whereas cerebrovascular disease, systolic blood pressure, and fasting glucose were associated with ΔHF% in patients aged ≥ 65 years. Conclusions: Our study demonstrated significant changes in HRV after HD in diabetic patients. In the patients aged ≥ 65 years, LF was increased, whereas HF% was decreased significantly after HD. Among the HRV parameters, age had an interaction with the change of HF%.